18.4 GHz evenly spaced flat multi-wavelength Brillouin–Raman comb fiber laser in the U-band region. (24th September 2021) - Soltanian, M R K; Long, P; Goher, Q S; Soltanian, M J K; Légaré, F
Abstract: We report on a double spaced Brillouin–Raman comb fiber laser covering the spectral range of 1654–1677 nm. A 3 W fiber laser source with center wavelength at 1545 nm is used as the Raman pump for a 2.6 km dispersion compensation fiber to generate peak Raman gain at 13.2 THz away from the Brillouin pump (BP) which is around 1655 nm. A 5 mW narrow linewidth laser diode is utilized as the BP to generate multiwavelength Brillouin–Raman comb fiber laser (MBRCFL). A stable MBRCFL is generated with maximum bandwidth of 23 nm which contains 136 Brillouin Stokes with 0.168 nm spacing between BP and first Stoke corresponding to 18.4 GHz frequency spacing, an average power of 340 mW and optical signal to noise ratio of 26 dB. The output power fluctuation of less than 4% is measured over a period of 4 h. Moreover, the slope efficiency of 34% is achieved while the flat-amplitude bandwidth of about 17 nm is observed.